2006
DOI: 10.1021/bi051992u
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol Monolaurate Inhibits the Effects of Gram-Positive Select Agents on Eukaryotic Cells

Abstract: Many exotoxins of gram positive bacteria, such as superantigens (staphylococcal enterotoxins, toxic shock syndrome toxin-1 [TSST-1], and streptococcal pyrogenic exotoxins) and anthrax toxin are bioterrorism agents that cause diseases by immunostimulation or cytotoxicity. Glycerol monolaurate (GML), a fatty acid monoester found naturally in humans, has been reported to prevent synthesis of gram positive bacterial exotoxins. This study explored the ability of GML to inhibit the effects of exotoxins on mammalian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 65 publications
(119 reference statements)
6
89
0
Order By: Relevance
“…However, we recently demonstrated that 5% GML gels, applied vaginally to monkeys, prevented simian immunodeficiency virus (SIV) transmission (16,24) by interference with epithelial cell production of proinflammatory cytokines that attract CD4 T cells into cervical/vaginal tissues. These data agree with prior studies that demonstrate that GML exerts membrane-stabilizing anti-inflammatory effects (21). In our study, GML anti-inflammatory effects are also likely to contribute to interference with VVC and BV.…”
Section: Discussionsupporting
confidence: 93%
“…However, we recently demonstrated that 5% GML gels, applied vaginally to monkeys, prevented simian immunodeficiency virus (SIV) transmission (16,24) by interference with epithelial cell production of proinflammatory cytokines that attract CD4 T cells into cervical/vaginal tissues. These data agree with prior studies that demonstrate that GML exerts membrane-stabilizing anti-inflammatory effects (21). In our study, GML anti-inflammatory effects are also likely to contribute to interference with VVC and BV.…”
Section: Discussionsupporting
confidence: 93%
“…These studies resulted in additional work that demonstrates that GML inhibits TSST-1 production through interference with bacterial signal transduction (300), reduces S. aureus and group B streptococci vaginally while selecting for the normal flora lactobacilli, and reduces vaginal inflammation as measured by reductions in IL-8 production (301); IL-8 is a chemokine that specifically attracts neutrophils to infection sites. In more recent studies, it has been shown that GML stabilizes and is anti-inflammatory to mucosal epithelial cells as well as other immune cells (302,303). The studies suggest that GML, in addition to preventing TSST-1 production, stabilize the host mucosa to prevent outside-in signaling (109).…”
Section: Preventing Superantigen Production By Mucosal Microbicides Amentioning
confidence: 99%
“…Other investigators have demonstrated that a laurate substituted dodecanoic acid monoester, glycerol monolaurate, retards bacterial virulence factor expression (8,15,20,25,33). An observed problem with glycerol monolaurate was that the ester bond was degraded by human and staphylococcal esterases and lipases, rendering low concentrations of the compound ineffective (20).…”
Section: Vol 53 2009 S Aureus Tsst-1 Inhibiting Compounds 1903mentioning
confidence: 99%